(untitled) - Csengeri, Istvan (Can Tho, Viet Nam, 1998)
The aim of this paper is used to train the researcher the necessary methods and skills for writing scientific papers. In addition, it guides them to publish the researches in different ways.
Keywords: Research,Nghiên cứu; Methodolog,Phương pháp